Avaliação da atividade gastroprotetora do farnesol em modelos animais - Pessôa, Michelle Liz de Souza (2023)
Farnesol is a product of natural origin, belonging to the class of sesquiterpenes, found in the essential oils of lemongrass (Cymbopogon citratus) and chamomile (Matricaria camomila), in citrus fruits and vegetables. Farnesol has antioxidant, anti-inflammatory, anxiolytic, antinociceptive, anti-obesity, antimicrobial, antitumor and antidiarrheal activities. However, there are no studies in the literature about its gastroprotective activity, which motivated the choice of this substance for this study. Thus, this work aimed to evaluate the non-clinical acute toxicity and the gastroprotective effect of farnesol in animal models. For this, a behavioral assessment was carried out, estimation of the 50% lethal dose (LD50), analysis of the gastroprotective effect with different models of acute induction by harmful agents (ethanol, stress, NSAIDs and pylorus ligation) at different doses and determination of the mechanisms of actions involved in this effect (antisecretory, cytoprotective, antioxidant and immunoregulatory). The results obtained suggest that farnesol has low toxicity, with an LD50 equal to or greater than 2,500 mg/kg according to OECD Guide No. 423. In the ethanol-induced ulcer protocol, farnesol (25, 50, 100 and 200 mg/kg, p.o.) showed a gastroprotective effect in 73%, 92%, 97% and 98%, respectively, reduced the ulcerative lesion index (ILU) (p < 0.001) compared to the control group (tween 80 5%). In injuries induced by strain and cold stress, farnesol at the same doses reduced the ILU (p < 0.001) by 29%, 38%, 54% and 54%, respectively, compared to the negative control. When inducing lesions with NSAIDs (piroxicam), farnesol (25, 50, 100 and 200 mg/kg, p.o.) reduced ILU by 10% (p < 0.05), 23%, 46% and 51% (p < 0.001) respectively, compared to the negative control. In the experimental protocol of pylorus ligation (gastric juice containment), farnesol (100 mg/kg, v.o. and i.d.) reduced ILU (p < 0.001) by oral and intraduodenal routes, did not change pH in both routes and on H+ concentration and volume of gastric juice orally. However, it reduced the concentration of H+, the volume of gastric juice in the intraduodenal route. Previous administration of NEM blockers (blocker of sulfhydryl groups), L-NAME (NO synthesis inhibitor) and glibenclamide (KATP channel blocker) and indomethacin (cyclooxygenase inhibitor) reduced the gastroprotection exerted by farnesol (p < 0.001), suggesting the participation of these pathways in their gastroprotective activity. Farnesol increased gastric mucus in stomach tissue, suggesting the participation of this pathway in its gastroprotective activity. Farnesol also showed antioxidant effects by increasing the concentration of GSH and SOD activity and reducing MDA levels and MPO activity, as well as demonstrating an immunomodulatory effect by reducing the pro-inflammatory cytokines IL-1β, IL-6 and TNF-α and increase the anti-inflammatory cytokine IL-10.